2006
DOI: 10.2214/ajr.04.1181
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Extrusion in Young Athletes: Associated Knee Joint Abnormalities

Abstract: Meniscal extrusion is a common finding on MRI of athletes' knees. Meniscal extrusion in association with meniscal tear and joint effusion is postulated as a significant injury in athletes and its recognition as such in this group is important because it may prompt orthopedic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 9 publications
2
53
1
Order By: Relevance
“…We demonstrated that meniscal tears are not the only factors associated with meniscal extrusion; other factors, such as tibiofemoral cartilage damage and knee malalignment, are independently associated with meniscal extrusion. The relationship between meniscal tears and meniscal extrusion has been explored previously (22)(23)(24)(25)(26)30). The intricately woven pattern of collagen fibrils is responsible for the strength of the meniscus, which maintains its shape and structure when axially loaded (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that meniscal tears are not the only factors associated with meniscal extrusion; other factors, such as tibiofemoral cartilage damage and knee malalignment, are independently associated with meniscal extrusion. The relationship between meniscal tears and meniscal extrusion has been explored previously (22)(23)(24)(25)(26)30). The intricately woven pattern of collagen fibrils is responsible for the strength of the meniscus, which maintains its shape and structure when axially loaded (43).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors may also be related to meniscal extrusion, even when no other meniscal pathologic findings are detected (25,26,33). Factors such as knee malalignment, tibiofemoral cartilage loss, and body mass index (BMI) might increase the load transmitted to the tibiofemoral compartments, and thus to the menisci, which may lead to meniscal extrusion.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, knee OA may lead to degenerative meniscal damage that may accelerate the disease process [8]. Meniscal tears are known to be associated with structural progression (increased cartilage loss) of knee OA [9][10][11] and with meniscal extrusion [12][13][14], defined as a difference ≥3 mm between the external meniscal margin and that of the tibial plateau. Meniscal extrusion also is also common in knees without OA [15].…”
Section: Introductionmentioning
confidence: 99%
“…This condition has been shown to frequently co-occur with meniscal (specifically root) tears [Costa et al, 2004;Lerer et al, 2004;Rennie and Finlay, 2006;Magee, 2008]. In epidemiological studies, meniscus extrusion (usually graded visually) and tears were found to be significantly associated with the incidence and progression [Hunter et al, 2006] of knee osteoarthritis (OA; i.e.…”
Section: Introductionmentioning
confidence: 99%